Teacher Educators and Expansive Learning in the Workplace and Beyond - Murray, Jean; Kidd, Warren; McMahon, Andrea; Viswarajan, Sheeba (Frontiers in Education, 2020)
Research on the professional learning of teacher educators is a relatively young and under-researched area, despite the importance of this occupational group in the fast-changing area of teacher education internationally. Past provision for learning has often focused on either one-off professional development events or workplace learning. Aiming to develop new knowledge and understanding of professional learning for teacher educators, this article attempts firstly, to analyse the impact of a one-off learning event, offered by the European InFo-TED group, on its participants, and secondly, to look at where and how the learning generated there developed further learning back in the workplace. Deploying a conceptual framework emphasising participatory professional learning and Engestrom’s concept of expansive learning, we explore how these two forms of learning might be planned and implemented in order to provide integrated, professionally relevant and enduring forms of learning.